EFEKTIFITAS PESTISIDA NABATI DAN BIOCHAR TERHADAP SERANGAN ULAT DAUN ( Plutella xylostella) PADA TANAMAN SELADA - Mawardiana Mawardiana; Karnilawati Karnilawati; Cut Nurlaili (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Until now, plant-based pesticides are rarely used by farmers because many do not know how to make them and think they are less effective in eradicating pests and diseases. This study aims to determine the level of effectiveness of vegetable pesticides and biochar against attacks on lettuce. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Jabal Ghafur Sigli University, from August to September 2020. This study used a factorial patterncheck-group design (RAK), there were 2 factors studied, namely the concentration factor of soursop leaf extract (P) and biochar (B). There are 3 levels of soursop leaf extract concentration factor, namely P1 = 15%/l water, P2 = 30%/l water, P3 = 45%/l water and biochar consists of 3 levels, namely B1 = 10 tons ha-1, B2 = 20 tons ha-1 , B3 = 30 tons ha-1. Parameters observed were attack intensity, mortality percentage, plant weight. The results showed that soursop leaf extract had a very significant effect on all variables, the intensity of attack decreased with increasing concentration of soursop leaf extract, as well as mortality reached 72.22% at the lowest concentration tested. attack and mortalityKeywords : Soursop Leaf, caterpillars, biochar, lettuce